Non-Meritrocratic Factors Affecting Filling Of Positions In Structural Institutions - Rois Alfianto; Ismi Dwi Astuti Nurhaeni Ismi Dwi Astuti Nurhaeni; Asal Wahyuni Erlin Mulyadi Asal Wahyuni Erlin Mulyadi (Al-Makki Publisher, 2023)
The government often use draft meritocracy To promote and hire official based on trend For doing work, record traces, and achievements other. Several big agencies No obey protocol. Paper This researches non-meritocratic aspects of institution structure in a manner thorough. Researchers also wonder about how much a good selection process meritocracy function For tasks structural public. Focus study This is knowledge administration about governance issues post-filling. Method Qualitative used in a study this. Three of the most influential non-meritocratic criteria For getting a position in Indonesia are interest in politics, interest in family, and love or No like. factors This appears Because condition established norms bureaucracy For taking a position.